Handbook of Closeness and Intimacy. - Mashek, Debra J. (Lawrence Erlbaum Associates, 2004)
The goal of this text is to bring together the latest thinking on the scientific study of closeness and intimacy from the most active and widely recognized relationship scholars in social and clinical psychology, communication studies, and related disciplines.